Strategi Komunikasi Pemasaran dalam Meningkatkan Kepercayaan Konsumen pada PT Albis Nusa Wisata di Jakarta - Muhammad Reza Pahlevi; Aminah Swarnawati (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
In competitive business competition, every company needs to develop an effective marketing communications strategy to attract potential consumers. This research aims to determine the marketing communication strategies that have been implemented by PT Albis Nusa Wisata Jakarta in increasing consumer trust. The theory used in this research is Marketing Communication theory; Marketing Communication Strategy; Consumer Confidence; Hajj and Umrah. This research methodology uses a qualitative approach with descriptive methods. Data collection techniques through in-depth interviews, observation, analysis and documentation. The technique for determining informants used purposive sampling, 2 informants were interviewed. Data analysis techniques are 1) data reduction; 2) data presentation; 3) drawing conclusions. Test the validity of the data using source triangulation. The results of this research found that PT Albis Nusa Wisata implemented 7 marketing communication strategy steps, such as determining marketing communication objectives, identifying target audiences, determining effective messages, choosing communication channels, managing marketing communication budgets, implementing and managing communication campaigns, and conducting evaluations and adjustment. In its implementation, there are several more prominent points in its implementation, namely determining communication objectives; determine effective messages; selection of communication channels, implementing and managing the campaign final evaluation and adjustments. However, there are aspects that need to be improved in PT Albis Nusa Wisata's marketing communications strategy. Target audience identification needs to be improved to be more targeted, and marketing communications budget settings need to be optimized.